(untitled) (Raparin Journal of Humanities (RJH), 2025)
Given the substantial influence of these variables on athletic performance, this study sought to determine the nature of the relationship between psychosomatic symptoms (such as anxiety, tension, and fear) and certain physiological functional variables (such as blood pressure, respiration, and pulse rate) among soccer players both in normal circumstances and prior to competing in sports. Since the descriptive approach is most suited to the nature of the issue, the researcher used it on a purposeful sample of twenty-two Peshmerga Sports Club players who are playing in the Kurdistan Premier League. Devices for detecting blood pressure and pulse as well as a psychological questionnaire created by Allawi (1987) to gauge psychosomatic symptoms were among the research instruments. There were two stages to the experiment: the first took place four days prior to the competition, and the second took place one hour before the competition. In both scenarios, the players’ answers to the psychosomatic symptom scale were examined, and functional data (blood pressure, respiration, and pulse) were noted. The researcher came to the following conclusions: - The psychosomatic symptoms scale shows significant differences between the normal and pre-competition states in favor of the pre-competition sports; - The functional variables (systolic blood pressure, diastolic blood pressure, respiration, and heart rate) show significant differences between the normal and pre-competition states in favor of the pre-competition sports. The researcher made the following recommendations in light of this: Because of its impact on the body’s systems, athletes’ psychological readiness must be guaranteed as a factor influencing their level of performance. Football players’ psychological characteristics can be objectively measured by using psychological scales. By holding intense and somber games and meetings, participants are acclimated to the competitive environment. The psychologist’s function in lowering pressure before a competition. Performing a comparable study on several athletic events using the same research methods and factors.